On stability of emulated turning processes in HIL environment. Issue 1 (2019) - Stepan, Gabor; Beri, Bence; Miklos, Akos; Wohlfart, Richard; Bachrathy, Daniel; Porempovics, Gabor; Toth, Andras; Takacs, Denes
Abstract: Hardware-in-the-loop (HIL) experimental setup is presented to investigate the stability of turning processes. A dummy workpiece is fixed to a main spindle, which is excited in the radial direction by electromagnetic contactless actuators. The actuators emulate contact force characteristics including surface regeneration effect between the cutting tool and the workpiece with 100 kHz sampling frequency. The cutting force is calculated by a high performance real time target that uses the measured present and previous values of the relative displacements of the dummy workpiece. The loss of linear stability is monitored for various real spindle speeds and virtual chip widths. Measured lobe diagrams are compared with the results of theoretical stability analysis.